A rare presentation of snake bite - Goswami, Sourabh; Keswani, Prakash; Sharma, Shrikant (International Journal of Research in Medical Sciences, 2019)
In India, doctor’s in casualty frequently get confronted with snake bite. A wide range of complications occur in snake bite. Intracerebral haemorrhage (ICH) is an unusual presentation following snake bite. Here authors discuss a patient presents with ICH after snake bite. Venom induced consumption coagulopathy is the most accepted theory behind intracerebral haemorrhage.